Analyzing John H. Hick’s Religious Pluralism and Its Implications from Islamic Ethical Perspectives - Kazeem , Akeem Olayinka; Shehu, Fatmir (Journal of Islamic Thought and Civilization, 2023)
This paper underscores religious pluralism postulated by John Hick (1922–2012) to (re)solve various perceived conflicts of religious diversity and inter-religious relationships in the modern times. To embark on the religious implications of Hick’s postulation from an Islamic standpoint with an emphasis on the ethical perspectives, this study discusses all the relevant conflicts arising due to the misrepresentation of certain issues in a religious context. Additionally, this research is eloquent as it highlights certain moral principles provided by Islam to address the real and potential conflicts of religious diversity and inter-religious issues without any apologetic view of Islamic core doctrines; this contrasts with Hick’s approach that implies a fundamental revision in the foundational doctrines of Islamic belief system. Therefore, to focus on the doctrinal, theological, and epistemic implications; concerning any attempt by the Muslims to adopt Hick’s view with special attention on Islamic ethics as the better alternative, this research analyzed various Qur’ānic verses. Furthermore, the study uses a qualitative method of interpretive and critical analysis approaches and the relevant Qur’ānic verses and previous studies to originate its sources of data from related research. Moreover, the paper concludes that an ethical approach to religious diversity and interreligious issues and conflicts is more pragmatic and effective based on Islamic perspectives other than Hick’s religious pluralism, which necessarily implies religious relativism, agnosticism, and skepticism that are antithetical to the Islamic worldview.